Regulations of phage therapy across the world - Yang, Qimao; Le, Shuai; Zhu, Tongyu; Wu, Nannan (Frontiers in Microbiology, 2023)
Phage therapy, a century-long treatment targeting bacterial infection, was widely abandoned after the clinical availability of antibiotics in the mid 20 th century. However, the crisis of antimicrobial resistance today led to its revival in many countries. While many articles dive into its clinical application now, little research is presenting phage therapy from a regulatory perspective. Here we focus on the regulations of phage therapy by dividing sections into Eastern Europe where it was never abandoned and Western Europe, Australia, the US, India, and China where it only re-attracted researchers' attention in recent decades. New insights about its regulations in China are provided as little English literature has specifically discussed this previously. Ultimately, by introducing the regulations in phage therapy for human health across representative countries, we hope to provide ideas of how countries may borrow each other's adapting legislation in phage therapy to best overcome the current regulatory hurdles.